2013
DOI: 10.1517/14656566.2014.869210
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase inhibitors in renal cell carcinoma

Abstract: VEGF TKI and m-TOR inhibitors have significantly improved the outcome of mRCC and offer a gain in survival by sequential treatments for the majority of patients. But they induce a particular toxicity profile. An adequate management of each drug and its sequence in treatment is essential to optimise the outcome and preserve the quality of life (QoL) of patients with mRCC. In forthcoming years, pending results should indicate whether VEGF TKI are of interest in an adjuvant setting and if new drugs targeting will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 88 publications
(56 reference statements)
0
7
0
Order By: Relevance
“…TKIs are administered primarily as anti-angiogenic treatment of solid tumors [20]. Clinical trials showed that in advanced RCC, TKIs such as sorafenib, sunitinib and pazopanib exert consistent therapeutic effects that prolong both OS and PFS [21, 22]. However, these targeted agents require new prognostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…TKIs are administered primarily as anti-angiogenic treatment of solid tumors [20]. Clinical trials showed that in advanced RCC, TKIs such as sorafenib, sunitinib and pazopanib exert consistent therapeutic effects that prolong both OS and PFS [21, 22]. However, these targeted agents require new prognostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…, anti-VEGF-A antibody (Bevacizumab), VEGFR2 TKIs (Sunitinib and Sorafenib), or mTOR inhibitors (Temsirolimus and Everolimus). Targeted drugs are especially important when chemotherapy is ineffective for RCCs and are often given as first-line treatment in metastatic disease [31] . However, there is no consensus on which drug is the best.…”
Section: Discussionmentioning
confidence: 99%
“…For example, drugs that target tyrosine kinases (TKIs; sorafenib, sunitinib, pazopanib, and axitinib) are designed to inhibit vascular endothelia growth factor (VEGF) and angiogenesis. 25,26 TKIs can work well in slowing the growth of kidney tumors, but their use can be associated with significant side-effects and tumor cell growth resumes when treatment stops. Selective tumor cell death can also result from use of TNFrelated apoptosis-inducing ligand (TRAIL).…”
Section: Tumoricidal Agentsmentioning
confidence: 99%